Historiosophy of the Russian revolution as a cultural phenomenon - A. V. Shestopal; M. V. Silantyeva (Концепт: философия, религия, культура, 2020)
Book review: Kozhokin E.M. 2020. Revoliutsiia i ee preodolenie: ocherki istorii rossiiskoi mental’nosti [The revolution and its overcoming: essays on the history of Russian mentality]. Moscow: MGIMO-Universitet. 270 p. (in Russian).